Book Review: Initial language teacher education - Fikri Yanda (IRecall Journal, 2023)
Within the last three decades, the discipline of initial language teacher education has undergone what is called as the Sociocultural Turn (Johnson, 2006). This shift necessitates considering teacher learning and professional development as a situated social and individual that is facilitated by opportunities for new teachers to acquire the mediational skills required to fully engage in teaching-focused communities of practice. At the practical level, much of what takes place in teacher education classrooms still follows traditional models that emphasize passing on to teacher candidates either pre-existing theories or pre-existing practices for teaching languages. Initial Language Teacher Education by Gabriel Díaz Maggioli, an academic advisor to the Institute of Education at Universidad ORT Uruguay, South America; the vice president of IATEFL, and an active member and contributor of TESOL International Association, describes the long process of becoming a language teacher. To Maggioli, this process includes a much more active and interactive attempt in which different levels of expertise are served. Through reciprocal, intentional scaffolds, the novice teachers are empowered to be able to practice theory while also theorizing practice.